Financial inclusion, poverty and territorial inequality in Ecuador - Álvarez-Gamboa, Javier (2022)
Financial inclusion has become very important in recent decades, due to its relevance and contribution to the economic development of countries. This article analyzes the relationship between financial inclusion and multidimensional poverty. Three spatial panel estimations are developed through the SAR, SEM and SARAR models, for which a synthetic index is constructed through variables that group the dimensions of access and use of financial inclusion by means of the multivariate technique of principal component analysis. The results indicate an inverse association between financial inclusion and poverty. Likewise, it was determined that there are marked territorial inequalities between Ecuador's provinces as reflected in the results obtained from the financial inclusion index measured in high, medium and low strata. It is concluded that financial inclusion is an important tool for development since it has the capacity to reduce poverty, which is why it is necessary for developing countries such as Ecuador to strengthen access to and use of financial products and services with special emphasis on excluded segments of the population in order to improve the living conditions of society.